"Slepi nemir človeštva" - Snoj, Vid (Primerjalna književnost, 2004)
"Blind unrest of humanity": Kocbek's poetic vision of history. The text is derived from a claim that Edvard Kocbek is a poet of history. It argues this claim by making the distinction between poetic depiction of history or its great deeds, and poetic verbalisation of history itself. This is illustrated on three poems by Kocbek: Zgodovina (History) from the collection Žerjavica (Embers), Trije modri (The Three Magi) form the collection Groza (Horror), and Molitev (Prayer) from the collection Žerjavica (Embers).
Keywords: Kocbek, Edvard, 1904-1981; slovenska poezija; zgodovina; history; čas; God; Bog